Awareness in undergraduate medical students regarding care and handling of experimental animals: A questionnaire based study - GITASHREE DUTTA; TARUN KUMAR; RITESH KUMAR; N. MEENA DEVI; PRIYOTOSH BANERJEE; P. SHYAMASAKHI DEVI (International Journal of Pharma and Bio Sciences, 2018)
The objective of the present study is to access the level of awareness among the under graduate (UG) medical students of RIMS regarding handling of experimental animals.The knowledge of animal experiment is one of the essential component for under graduate medical students in their education curriculum and they spend a good amount of time on that To understand it’s importance we conducted the cross sectional questionnaire based study to determine the awareness status on handling of experimental animals among the MBBS and BDS students of RIMS, Imphal, Manipur, Indiafrom 21st December, 2017 to 20th January, 2018. Prior to the study initiation, an informed verbal consent was taken from the students. The participants were briefly explained about the study and its importance and asked to join the same. The data was collected by questionnaire method. Descriptive statistics were used. Chi square test was used to test for association between proportions of the data and p value of <0.05 was considered significant.Out of total participants, 76.9% were MBBS students and 23.1% were BDS students. Also 57.7% participants were male and 42.3% were female in total participants. Only 16.5% students were found to have adequate awareness,out of which MBBS students were found to have more awareness than BDS students and were statistically significant with p-value of 0.013. By this study we concluded that UG students had inadequate level of awareness regarding handling of experimental animals.So there should be a provision of extra classes to create awareness among the students.